Analisis Pengaruh Social Media Marketing Terhadap Niat Menabung Melalui Brand Image (Studi Pada Bprs Magetan) - Citra Setyoningrum; Yessy Artanti; Sanaji Sanaji (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was to find how social media marketing influences the saving intentions through the brand image of BPRS Magetan. The population in this research is BPRS Magetan financing customers. This research uses the Structural Equation Model method to measure the influence between the independent variable and the dependent variable. Respondents are BPRS Magetan financing customers who have Instagram accounts. Data were collected using a questionnaire distributed to 103 respondents via Google Form. The results achieved in this research were the discovery of the influence of social media marketing on brand image and brand image on the intention to save. However, it was found that social media marketing had no effect on savings intentions.